2011
DOI: 10.1182/asheducation-2011.1.143
|View full text |Cite
|
Sign up to set email alerts
|

How I Diagnose and Manage HIT

Abstract: Heparin-induced thrombocytopenia (HIT) is a prothrombotic drug reaction caused by platelet-activating IgG antibodies that recognize platelet factor 4 (PF4)/polyanion complexes. Platelet activation assays, such as the serotonin-release assay, are superior to PF4-dependent immunoassays in discerning which heparin-induced antibodies are clinically relevant. When HIT is strongly suspected, standard practice includes substituting heparin with an alternative anticoagulant; the 2 US-approved agents are the direct thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
153
0
6

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 136 publications
(167 citation statements)
references
References 40 publications
7
153
0
6
Order By: Relevance
“…presented a tabular summary of the experience with fondaparinux in patients with clinical and laboratory evidence of HIT (all of the patients were at least EIA positive); there were 52 patients reported (from 4 studies), of whom 34 (65%) had HIT-associated thrombosis. 2 Remarkably, none of the 52 patients had evidence of new, progressive, or recurrent thrombosis, data similar to what we observed with rivaroxaban (0 of 52 vs 1 of 46). In 2008, the American College of Chest Physicians Evidence-Based Clinical Practice Guidelines suggested that fondaparinux was a reasonable treatment option for HIT, albeit as a weak (ie, grade 2C) recommendation based on retrospective observational data.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…presented a tabular summary of the experience with fondaparinux in patients with clinical and laboratory evidence of HIT (all of the patients were at least EIA positive); there were 52 patients reported (from 4 studies), of whom 34 (65%) had HIT-associated thrombosis. 2 Remarkably, none of the 52 patients had evidence of new, progressive, or recurrent thrombosis, data similar to what we observed with rivaroxaban (0 of 52 vs 1 of 46). In 2008, the American College of Chest Physicians Evidence-Based Clinical Practice Guidelines suggested that fondaparinux was a reasonable treatment option for HIT, albeit as a weak (ie, grade 2C) recommendation based on retrospective observational data.…”
Section: Discussionsupporting
confidence: 74%
“…[1][2][3] To date, treatment options during acute HIT have focused on parenteral anticoagulants, either on-label, such as argatroban or (in non-US jurisdictions) danaparoid, or off-label, such as fondaparinux or bivalirudin. [1][2][3][4][5][6] When longer-term anticoagulation is required, usually because of the presence of HIT-associated thrombosis, transition is often made from parenteral anticoagulation to a vitamin K antagonist (VKA) such as warfarin after platelet count recovery. (Earlier transition to VKA therapy is avoided because of increased risk of warfarin-induced microthrombosis during acute HIT.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the results of both the EIA and SRA tests, HIT antibody testing was reported as EIA-negative/SRA-negative (true-negative HIT test) indicating the absence of anti-PF4/heparin antibodies; EIA-positive/SRAnegative (presumed false-positive HIT test) indicating the presence of non-platelet activating anti-PF4/heparin antibodies; EIA-positive/SRA-positive (true-positive HIT test) indicating the presence of heparin-dependent platelet-activating anti-PF4/ heparin antibodies and the highest positive predictive value for clinical HIT [9,13]; EIA-negative/SRA-positive is a rare occurrence, indicating the possibility of heparin-dependent platelet activating antibodies that were not detected in the IgGspecific anti-PF4/heparin EIA and presumed false-positive SRA results. Indeterminate results, which were defined as reactivity in the SRA that did not fit a pattern compatible with HIT and did not demonstrate heparin dependence, comprised 4% of all samples and were not included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The lack of a rapid test that is specific for the diagnosis of HIT is a limitation of current management strategies. The serotonin-release assay (SRA), a functional assay, has the highest specificity for clinically apparent HIT [10][11][12][13], but because of its complexity, it is available only in a few reference laboratories. Immunoassays such as the anti-platelet factor 4 (PF4)/heparin enzyme-immunoassay (EIA) are commonly used as a screening test for HIT because they have a high sensitivity (>99%) and are readily available.…”
Section: Introductionmentioning
confidence: 99%
“…A fondaparinux (szubkután adandó szintetikus FXa-gátló) HIT-ben történt "off-label" alkalmazásáról már jelentek meg közlemények. Warkentin szerint 52, akut HIT-ben szenvedő betegnek adva egyiken sem alakult ki újabb thromboticus esemény [37]. Mivel a törzskönyvezett gyógyszerek "off-label" alkalmazása megengedett, szá-míthatunk arra, hogy a rivaroxaban és a dabigatran alkalmazásával kapcsolatos vizsgálatok eredményei is hamarosan közlésre kerülnek.…”
Section: Heparin Indukálta Thrombocytopenia (Hit)unclassified